Superresolution ISAR imaging by 2-D complex asymmetric half-plane lattice predictors - Erer, I.; Kartal, M.; Kayran, A.H. (IEEE, 2002)
An efficient algorithm to obtain high resolution ISAR images in the case of limited frequency band and small angular section is presented. The method is based on the 2-D autoregressive asymmetric half-plane modeling of the backscattered data using a 2-D complex lattice predictor. The locations of the scattering centers are determined by the zeroes of the transfer function of the prediction error filter. A simulation example is included to show the performance of the algorithm.